The Effect Of Focusing Care On The Patient And Its Reflection On The Patient Psychologically And Physically 2023 (Journal of Namibian Studies : History Politics Culture, 2023)
The aim of the research is to exaamine the effect of person-centered care on the patient and its reflection to the patient psychologically and physically together with the satisfaction of the patients. The study is a descriptive research. The population of the study consists of the patients who received services between June and August 2020. Of the work, in Balıkesir Saglik Bilimleri ,   Hospital Physiotherapy and Rehabilitation Practices Office, the patient collective was working face-to-face. The sampling method was determined by the Treatment and Rehabilitation Program, and considering the intensity of the daily work, it aims to reach the target number of study with 100 patients. In line with the data obtained from the research, the conclusion section is reached with the final evaluation part, and suggestions are made in line with this. ( .2020)